2022
DOI: 10.1523/jneurosci.2494-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Electric Properties and Diversity of Oxytocin Neurons in Paraventricular Nucleus of Hypothalamus in Female and Male Mice

Abstract: Oxytocin (OXT) neurons in paraventricular nucleus of hypothalamus (PVN) are involved in modulating multiple functions, including social, maternal, feeding, and emotional related behaviors. PVN OXT neurons are canonically classified into magnocellular (Magno) and parvocellular (Parvo) subtypes. However, morpho-electric properties and the diversity of PVN OXT neurons are not well investigated. In this study, we profiled the morpho-electric properties of PVN OXT neurons by combining transgenic mice, electrophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…Though previous studies suggested that oxytocin system could act differently in males and females [ 13 , 73 75 ], the neuronal properties and projections of PVN oxytocin neurons are found to be sex invariance in mice [ 76 , 77 ], and the modulation function of oxytocin signal in visual cortex was reported to be similar in different genders [ 15 , 16 ]. In our study, we compared the differences in retinal oxytocin signals between males and females in the following four aspects: (1) Oxtr fluorescence intensities in the INL and GCL are not significantly different between males and females (Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Though previous studies suggested that oxytocin system could act differently in males and females [ 13 , 73 75 ], the neuronal properties and projections of PVN oxytocin neurons are found to be sex invariance in mice [ 76 , 77 ], and the modulation function of oxytocin signal in visual cortex was reported to be similar in different genders [ 15 , 16 ]. In our study, we compared the differences in retinal oxytocin signals between males and females in the following four aspects: (1) Oxtr fluorescence intensities in the INL and GCL are not significantly different between males and females (Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Acute brain slices were prepared from mice as previously described [ 43 45 ]. Neurons were visualized in slices using an IR/DIC microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to other hypothalamic neurons including preautonomic (Stern, 2001), perinuclear zone (Armstrong and Stern, 1997) and GnRH neurons (Campbell et al, 2005;Herbison, 2021), MNNs have unique and distinctive morphological features, including a relatively large soma [dimensions up to 25-30 µm by 16-17 µm, membrane area ∼1,100-1,500 µm 2 (Stern and Armstrong, 1998;Chen et al, 2022)] from where a relatively simple dendritic arborization emerges. MNNs have typically 1-3 primary dendrites (Stern and Armstrong, 1998;Chen et al, 2022) that ramified on average to no more than six levels (Stern and Armstrong, 1998) and have path lengths up to 300-500 µm (Stern and Armstrong, 1998). Moreover, MNNs contain specialized enlargements or swellings named varicosities (Stern, 2001;Ludwig and Stern, 2015), in which most of the neuropeptide cargo is stored, and from where release is believed to occur (Ludwig and Leng, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Consequences of such remodeling of neuron-glia microgeometry for neurons functioning remain poorly understood and thus attracted our attention in this study referring exclusively to astrocytes (and using general term "glia" as a synonym). Based on available data 10.3389/fncel.2023.1125029 describing MNN microgeometry (Smith and Armstrong, 1990;Stern and Armstrong, 1998;Chen et al, 2022), we built biologically inspired cell models and explored geometry-related features of the somato-dendritic passive transfer of voltages and currents. To derive and solve model equations, we used methods of the theory of electro-geometrical coupling and parametric sensitivity of the dendritic transfer functions, which were systematically described earlier Kaspirzhny, 2008, 2011;Korogod and Tyc-Dumont, 2009).…”
Section: Introductionmentioning
confidence: 99%